IMPLEMENTATION OF THE REGULATION OF THE MINISTER OF PPPA NO. 6 OF 2015 CONCERNING THE ROLE OF THE OFFICE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION DURING THE COVID-19 PANDEMIC IN SAMARINDA CITY - Turah Nurul Aini; Marwiah Marwiah; Suryaningsi Suryaningsi (Faculty of Teacher Training and Education, Mulawarman University, 2021)
To create a just society, the government develops programs that have been planned, one of which is to provide protection to women and children as the nation's next generation. During the COVID-19 pandemic, many cases occurred to women and children so that the role of the government was needed. 6 of 2015 concerning the Women's Empowerment and Child Protection System, and more violence in the role. This study uses a qualitative method with a descriptive approach. With resource persons who have the criteria. Using data collection techniques, namely observation, interviews, and documentation as well as data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Based on the results of the study indicate that the implementation of the Minister of PPPA Regulation No. 6 of 2015 concerning the Role of the Office of Women's Empowerment and Child Protection during the COVID-19 Pandemic in Samarinda City has gone well with the existence of the Integrated Service Center for Women's Empowerment and Child Protection (P2TP2A) and has changed since 2019 into an Integrated Implementation Unit for Women's Protection Areas and Children (UPTD PPA) with the issuance of Regulation of the Minister of PPPA No. 4 of 2018. The implementation and role of the Office has been running smoothly through the P2TP2A institution to become UPTD PPA. Suggestions for research that can be done is to propose to the Regional Government to issue a budget for the construction of Safe Houses to provide services.